Political Risk: A Review and Reconsideration - Kobrin, Stephen J. (Journal of International Business Studies, 1979)
This paper has three objectives: First, to review the literature dealing with the assessment and evaluation of political risk by managers in international firms. Second, to build upon this literature by extending and more precisely defining the concept in a manner that facilitates integration into the planning or decision–making process. Last, the paper attempts to suggest fruitful directions for future research.